Reseller Loyalty as an Asset for MSMEs: An Analysis of Product Quality and Consumer Demand - Aji Priambodo (Jurnal Simki Economic, 2024)
Loyalty of resellers is very important because it plays a key role in the sustainability and growth of the business. Zaya Food is a micro, small, and medium enterprise (MSMe) located in Purbalingga, Central Java, which specializes in producing dried potatoes. In an effort to understand its business dynamics, a study was conducted involving 53 respondents who are resellers of Zaya Food products. This research aims to analyze the influence of various variables on reseller loyalty. The results show that all independent variables studied have a positive and significant impact on the dependent variable, namely reseller loyalty. This means that product quality, consumer demand, and other factors studied contribute significantly to building loyalty among resellers towards Zaya Food. Thus, improving product quality and gaining a better understanding of market demand can be effective strategies to enhance reseller loyalty. These findings are important for Zaya Food to continue innovating and maintaining product quality to sustain and improve good relationships with resellers, which in turn will support the growth of this MSMe in a competitive market.